Perspektif Penanganan Bullying Berdasarkan Paradigma Konseling Kognitif Perilaku MA - M Akmal Yazdy Ihsany; Najlatun Naqiyah; Bakhrudin All Habsy (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The cognitive-behavioral framework in addressing bullying emphasizes assisting both victims and perpetrators in recognizing and altering negative thought patterns and harmful behaviors, utilizing approaches that foster emotional and social change. This study seeks to examine approaches to managing bullying based on the cognitive-behavioral framework in MA. The research employs a qualitative methodology, using a literature review approach. The findings show that bullying involves intentional harm directed at others through power abuse, manifesting in forms like physical, verbal, social, and cyberbullying. Key roles identified in these dynamics include the perpetrator (bullies), the victim, the bully-victim (those who play dual roles), and neutral parties. Contributing factors to bullying range from internal elements, such as low self-esteem and difficulty interpreting situations, to external influences, including unsupportive social environments. The scope of bullying encompasses aggressive actions that must be recognized and managed to safeguard victims. The cognitive-behavioral framework proves effective in addressing bullying by focusing on the interplay of thoughts, emotions, and behaviors. Intervention strategies include establishing strong therapeutic relationships, recognizing dysfunctional thought patterns, and assigning between-session tasks. Techniques like self-awareness and self-regulation empower students to better identify their emotions and manage responses to bullying. Enhancing self-awareness and control helps reduce stress and fosters a more positive environment for student well-being. This research offers valuable insights for dealing with bullying in religious-based educational settings, especially through the use of structured and systematic cognitive-behavioral interventions.